The Efficacy and Outcome of a Two-Staged Operation for Irreducible Knee Dislocation: A Prospective Short-Term Follow-Up - Cui, Shengyu; Yi, Hong; Zhu, Xinhui; Fan, Jianbo; Ding, Yi; Liu, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Irreducible knee dislocation (IKD) is a very rare but serious type of knee dislocation, it can lead to soft tissue necrosis due to incarceration of the medial structures, and faces great difficulty in the post-operative rehabilitation, too. IKD needs careful preoperative planning. There is no universal agreement about the appropriate surgical strategy for IKD. The purpose of this study is to investigate the clinical efficacy, safety, and the outcome of the two-staged operation on treatment of IKD. Methods: IKD Patients were included from June 1, 2016 to May 31, 2020. In the stage-1 surgery, acute reduction and extra-articular structure repair were performed. Following an intermediate rehabilitation, delayed cruciate ligament reconstructions were performed in the stage-2. The physical examination, CT, MRI, X-ray were performed during peri-operative period. Knee function, joint stability, ligament laxity, knee range of motion (ROM) and alignment were accessed at follow-ups. The minimum and maximum follow-up time was 0.5y and 1y. Results: 17 IKD patients were included. 3 subjects (17.65%) missed at 1y follow-up, and the averaged follow-up was 11.18±2.53 months. After stage-1, normal alignment and superior valgus/varus stability were restored in most subjects, however, a notable anterior-posterior instability still existed in most patients. The intermediate rehabilitation processed smoothly (6.94±1.20 weeks), and all patients achieved knee ROM of 0-120° finally. At 0.5y and 1y follow-up after the stage-2, all subjects had achieved normal knee stability, ROM, as well as satisfying joint function. No infection or DVT was observed. Conclusions: The two-staged operation for IKD has the superior efficacy on knee stability and function, and it can facilitate the rehabilitation and achieve satisfactory short-term outcome. Level of Evidence : Level 3.